Investigating Axisymmetric and Asymmetric Signals of Secondary Eyewall Formation Using Observations‐Based Modeling of the Tropical Cyclone Boundary Layer. Issue 16 (16th August 2021) - Yu, Chau‐Lam; Didlake, Anthony C.; Kepert, Jeffrey D.; Zhang, Fuqing
Abstract: This study examines axisymmetric and asymmetric aspects of secondary eyewall formation (SEF) in tropical cyclones (TCs) by applying a nonlinear boundary layer model to tangential wind composites of observed TCs with and without SEF. SEF storms were further analyzed at times prior to and after SEF, as defined by the emergence of a secondary maximum in axisymmetric tangential wind. The model is used to investigate the steady‐state boundary layer response to the free‐tropospheric pressure forcing derived from observed tangential wind fields. The axisymmetric response to the Post‐SEF wind field displayed a secondary updraft maximum associated with a mature secondary eyewall; the model correctly produced no secondary updraft for non‐SEF storms. The Pre‐SEF response also exhibited a secondary updraft associated with an incipient secondary eyewall largely due to the broadened outer tangential wind field that commonly precedes SEF events. The asymmetric wind fields and model response were analyzed relative to the 850–200 hPa environmental wind shear vector. In Pre‐SEF storms, the tangential wind field displayed a broadened tangential wind structure in the downshear quadrants. The boundary layer response shows a downwind shift toward the left‐of‐shear quadrants, exhibiting the clearest secondary maxima in updrafts, tangential wind, and radial inflow. This left‐of‐shear response was the leading contributor to the secondary eyewall signals in the Pre‐SEF axisymmetric response. Sensitivity analyses confirmed the robustness of these asymmetric signals. These findings suggest that enhanced tangential wind and boundary layer updrafts in the left‐of‐shear sectors may be early indicators and critical features of SEF in sheared TCs. Plain Language Summary: SEF in TCs marks the beginning of an eyewall replacement cycle, a process that has impacts on the storm intensity and structure. The initiation of the SEF process is generally not well‐forecasted or fully understood. This study uses airborne observations and a nonlinear numerical model to examine the role of the boundary layer during SEF. We find that the earliest boundary layer signs of SEF are clearest in the left‐of‐shear sectors. We also show that these early left‐of‐shear signals of SEF are robust and systematically stronger than that of the other sectors, indicating that these sectors are the preferred location where initiation of SEF repeatedly occurs in these observed cases. The results of this study provide new insight to the evolution of TCs and can be potentially used for improving TC forecasts. Key Points: Airborne observations in tropical cyclones successfully force a nonlinear boundary layer model to simulate meaningful response features A broadened wind field prior to secondary eyewall formation (SEF) produces an updraft maximum associated with an incipient secondary eyewall The updraft maximum is strongest left of the shear vector, suggesting that this region plays an early role in SEF